Analisis Perilaku Konsumen Dalam Pengambilan KeputusanMemilih Layanan Service Komputer di CV.Rineo Nias Persada Kota Gunungsitoli - restu Zega; Yupiter Mendrofa; Emanuel Zebua; Eliagus Telaumbanua (LPPM Universitas HKBP Nommensen, 2024)
Consumer behavior greatly influences decisions regarding purchases or services. It is highly recommended for a company to know its target market and know and learn about consumer behavior first so that the marketing of its products or services can be maximized. In the research, the main problem is consumer behavior in responding to consumer needs in consumer decision making. The aim of this research is to determine consumer behavior in choosing computer service at CV. Rineo Nias Persada Gunungsitoli city, to find out decision making in choosing computer service services at CV. Rineo Nias Persada Gunungsitoli city and to find out the factors that influence consumer behavior in making decisions about choosing computer service services at CV. Rineo Nias Persada, Gunungsitoli city. The research uses qualitative research. Data collection techniques are observation, documentation and interviews. Data analysis techniques using data reduction, data presentation and drawing conclusions. The research results obtained from the data collection were analyzed using consumer behavior analysis in drawing conclusions. Based on the results of research carried out by researchers at CV. Rineo Nias Persada Gunungsitoli City, from the results of the research analysis previously stated, namely from the analysis of consumer behavior in making decisions about choosing computer service services at CV. Rineo Nias Persada Gunungsitoli City is that consumers consider several important factors, namely cultural, social, personal and psychological factors, where these factors play an important role in influencing consumer purchasing decisions in choosing computer service services.